CLINICAL PROBLEMS OF DIRECT DOSIMETRY (IN VIVO) IN CONTACT RADIATION THERAPY - V. A. Titova; D. A. Kokontsev; T. S. Belle (Biomedical Photonics, 2018)
The use of multicomponent methods of special treatment (surgery, polychemotherapy, radiation therapy, laser photodynamic therapy) in oncology requires the control of doses in the tumor and healthy organs with high accuracy. A method of direct dosimetry using fiber-optic scintillation dosimeter MCD-4 is proposed. The dosimeter is fixed on endostats and is visualized on CT/MRI. The coordinates are entered into the anatomical units and dosimetry calculations, the data are mapped, the doses are adjusted on medical grounds. The developed technique of direct dosimetry allows monitoring of the contact radiation therapy (CRT) procedure in real time and making the necessary changes and corrections during the treatment. The refinement of the absorbed dose values using calculations and direct dosimetry minimizes the risk of complications and ensures the possibility of effective use of other treatment methods, including photodynamic therapy, after CRT.